Heterose em híbridos de jiló para o mercado paulista - Souza, Jéssica Eliana Nogueira de (2016)
Gilo or African eggplant (Solanum gilo Raddi) is a vegetable characterized by its bitter taste and in Brazil there are cultivars of dark-green roundish (São Paulo market) and light-green long fruits (Minas Gerais, Goiás and Rio de Janeiro markets). Open pollinated cultivars are predominated used once that practically there is no commercial hybrids available. This work aimed to analyse the heterosis in African eggplant hybrids with potential to be incorporated at the São Paulo Market. It was used lines to obtain 17 experimental hybrids. The trial comprised the hybrids, their parentlines and more four checks. Traits under study were total and early fruits yield (t.ha-1), mean fruit mass (g/fruit), fruit length/diameter ratioand fruit coloring (Hue angle, chroma e lightness). Diallel analysis was performed using the partial diallel model adapted by Miranda Filho e Geraldi (1984), of lines of dark-green fruits. It was evaluated General combining ability (CGA) and specific combining ability (ECA) as well as varietal and heterosis effects. Heterosis was pronounced for total and early yields, but it had a low magnitude for fruit mass, fruit length, fruit length/diameter ratio and coloring. The F1(JIL-012-09 x JIL-013) hybrid had a good performance for all traits evaluated, thus, it standing out from the other hybrids and showing commercially competitive for São Paulo market. In the diallel analysis, the additive gene effects were more important than non-additive effects for all traits studied. Considering total and early yields, the parent lines presented similar behavior for CGA. The line 1 = BGH-4150-1-04-04 showed low CGA for mean fruit mass contributing for decrease the fruit mass, whereas, the line 2’= JIL-013 had a good performance. The parent lines showed a good performance or length/diameter ratio, except the line 1 = BGH-4150-1-04-04 which the ĝi estimate did not contribute to decrease fruit length/diameter ratio and that is not desirable. The CGA estimates for Hue angle did not differ from zero indicating that the lines are similar. For Chroma e Lightness the parent lines 4 = JIX-006C-154-1-05-05 and 1’= JIL-012-09 presented the best performance and they contribute to decrease the saturation and lightness at the fruit color, which is desirable.